1993
DOI: 10.1021/bp00022a010
|View full text |Cite
|
Sign up to set email alerts
|

Sub‐Micrometer‐Sized Biodegradable Particles of Poly(L‐Lactic Acid) via the Gas Antisolvent Spray Precipitation Process

Abstract: Sub-micrometer-sized particles of poly(L-lactic acid) may be formed by using near-critical or supercritical carbon dioxide as an antisolvent to precipitate poly(L-lactic acid) from droplets of methylene chloride solution sprayed into a carbon dioxide continuous phase. Particle sizes may be controlled by varying the density of the carbon dioxide; at constant temperature in the supercritical region, higher carbon dioxide densities yield larger particles. Two methods (one batch and one continuous) for introducing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
121
2

Year Published

1997
1997
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(130 citation statements)
references
References 30 publications
7
121
2
Order By: Relevance
“…When the solvent content has been reduced to the desired level, the vessel is depressurized and the solid product is collected. In a modified version of the SAS technique [92], the solid of interest is first dissolved in a suitable solvent and then this solution is rapidly introduced into the supercritical fluid through a narrow nozzle. The supercritical fluid completely extracts the solvent, causing the super critical fluid insoluble solid to precipitate as fine particles.…”
Section: Supercritical Anti-solvent (Sas) Methodsmentioning
confidence: 99%
“…When the solvent content has been reduced to the desired level, the vessel is depressurized and the solid product is collected. In a modified version of the SAS technique [92], the solid of interest is first dissolved in a suitable solvent and then this solution is rapidly introduced into the supercritical fluid through a narrow nozzle. The supercritical fluid completely extracts the solvent, causing the super critical fluid insoluble solid to precipitate as fine particles.…”
Section: Supercritical Anti-solvent (Sas) Methodsmentioning
confidence: 99%
“…Other authors (Chang et al, 2008;Gokhale et al, 2007;Obrzut et al, 2007;Reverchon et al, 2008) did not find relevant differences in the various precipitates obtained. Particularly, PLA morphologies showed to be insensitive to the SAS processing conditions (Randolph et al, 1993). This characteristic fact could be assigned to the high molecular weights and the tendency to form aggregated particles because of the reduction of the glass transition temperature in SC-CO 2 .…”
Section: Morphologymentioning
confidence: 95%
“…Moussa et al (Moussa et al, 2005) showed that the pressure distribution during the expansion of the supercritical fluid is a function of the nozzle length and diameter. Other authors used small internal diameter capillaries (Dixon et al, 1993;Randolph et al, 1993). Coaxial devices have also been proposed: in the SEDS process (solution enhanced dispersion by supercritical fluids) a coaxial twin-fluid nozzle to co-introduce the SCF antisolvent and solution is used (Bałdyga et al, 2010;He et al, 2010;Mawson et al, 1997;Wena et al, 2010).…”
Section: Parameters Influence On Hydrodynamicmentioning
confidence: 99%
“…During the SAS process, the Weber number is very high compared with that in other techniques. 12,28,40,56,63 The solubility of high-molecular-weight drugs in the supercritical fluid is related to the density. The solubility increases at higher densities and the effect of density on particle solubility is rapidly enhanced at higher densities.…”
Section: Effects Of Pressure and Temperaturementioning
confidence: 99%
“…Rapid mass transfer of antisolvent and solvent causes high supersaturations for the solute. 56 High supersaturation results in rapid nucleation and growth of more than one particle per primary droplet. 71 The solubility of supercritical CO 2 will vary with pressure.…”
Section: Effects Of Pressure and Temperaturementioning
confidence: 99%